2000
DOI: 10.4049/jimmunol.164.8.4244
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQ Tetramers Identify Epitope-Specific T Cells in Peripheral Blood of Herpes Simplex Virus Type 2-Infected Individuals: Direct Detection of Immunodominant Antigen-Responsive Cells

Abstract: Ag-specific CD4+ T cells are present in peripheral blood in low frequency, where they undergo recruitment and expansion during immune responses and in the pathogenesis of numerous autoimmune diseases. MHC tetramers, which constitute a labeled MHC-peptide ligand suitable for binding to the Ag-specific receptor on T cells, provide a novel approach for the detection and characterization of such rare cells. In this study, we utilized this technology to identify HLA DQ-restricted Ag-specific T cells in the peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 23 publications
6
90
1
Order By: Relevance
“…Class II molecules, however, are noncovalent dimers of α and β chains that display variable stability in solution (20). To reliably generate stable class II molecules in soluble form, Kwok et al have constructed class II molecules incorporating leucine zipper motifs that replace the transmembrane and cytoplasmic portions of the molecules (10,21). The advantage of this approach, with respect to others involving the synthesis of covalent single-chain class II/peptide molecules (22), is that empty class II molecules can be loaded with any selected peptide, increasing tremendously the number of epitopes that can be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Class II molecules, however, are noncovalent dimers of α and β chains that display variable stability in solution (20). To reliably generate stable class II molecules in soluble form, Kwok et al have constructed class II molecules incorporating leucine zipper motifs that replace the transmembrane and cytoplasmic portions of the molecules (10,21). The advantage of this approach, with respect to others involving the synthesis of covalent single-chain class II/peptide molecules (22), is that empty class II molecules can be loaded with any selected peptide, increasing tremendously the number of epitopes that can be studied.…”
Section: Discussionmentioning
confidence: 99%
“…For assay of viral antigenic epitopes, we have previously shown that stimulation with UV-inactivated virus is effective a Underlined residue is the proposed first anchor for binding to the respective allele as determined by peptide truncation studies (data not shown). (19). Similarly, peptide pools can be used for initial stimulation in the event that whole Ag is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Peptide-loaded tetramers were produced as described previously (15). Briefly, recombinant DRB1*0401, in which the transmembrane domain was replaced by a leucine zipper, were produced in Drosophila S2 cells.…”
Section: Tetramer Stainingmentioning
confidence: 99%